Effectiveness of an Educational Program on Nurses’ Knowledge and Practice toward Delirium Assessment of Patients at Critical Care Units in Baghdad Teaching Hospitals - H. Hamzah, Budour; A. Mansour, Khalida (International Journal of Psychosocial Rehabilitation, 2020)
Objective(s): The study aims to determine the effectiveness of the nursing education program on nurses’ knowledge and practice toward delirium assessment at critical Care Units in Baghdad Teaching Hospitals. Methodology: A quasi-experimental design study was conducted in Baghdad Teaching hospitals from the period 25th November 2019 to 13th August 2020. Non- probability (purposive) sample of (80) nurses who are working in the Intensive care units and High Dependency Unit and selected from the Directorate of Medical City, Nursing Home Hospital, Ghazi AL Hariri Teaching Hospital, Baghdad Teaching Hospital. The sample is divided into two groups; (40) nurses (the study group) are exposed to the educational program and (40) nurses (control group) are not exposed to the program. The researcher constructed educational program and instruments in order to reach the aims of the present study. The program deal with 5 main domains related to delirium assessment. The reliability of the instrument was determined through the use of the test-retest approach for the knowledge test and inter-observer for nurses’ practice. While the instrument validity determined through content validity by a panel of experts. Data were analyzed through the use of Statistical Package for Social Sciences (SPSS) version (21) by the application of descriptive statistics (frequency, percentage, arithmetic mean, standard deviations) and inferential statistic (chi – square, independent sample t-tests, paired t-test and one way ANOVA). Results: The current study revealed that nurses who participated in educational program demonstrated a high level of knowledge than the control group, in relation to delirium assessment include information about delirium, delirium assessment, sedation assessment, delirium prevention, and delirium management. Regarding nurses’ practice toward delirium assessment, the educational program had a positive effect on nurses’ practice as compared with a control group in relation to all delirium assessment domains. Recommendations: Based on the findings of the present study, the researcher recommends establishing training courses, seminars, and aperiodic performance assessment for nurses regarding delirium assessment in the intensive care units and it is recommended for future research conduction.